Crisis Aspects of the Bulgarian Democracy: Civic Participation and Political Representation - Asenov, Simeon (Research Papers, 2021)
The paper reveals the state and growing distrust towards democracy in Bulgaria. The crisis processes in civic participation, parties and political representation are analysed. Their cause and effect relationship and their negative impact on the democratic process in Bulgaria are identified. Possible approaches are proposed to alleviate the democratic crisis and its manifestations. In methodological aspect, the paper adheres to the political analysis that combines theoretical conclusions and empirical data and assessments of the researched problems.